Studi Literatur: Perbandingan Efektifitas Biogas dari Kotoran Sapi dan Sampah Sisa Sayur atau Buah - Taufik Dani; Purwanto; Sudarno Utomo (Yayasan Literasi Sains Indonesia, 2024)
This study aims to compare the effectiveness of biogas from cow dung and vegetable or fruit waste materials. The research method in this study uses literature studies or literature reviews from several accredited journals and articles that match the screening criteria. This literature study was conducted through a search for scientific publications in the 2015-2023 range using the Google Schollar and Elvieser Journal websites. A total of 15 journal articles that match the criteria and themes discussed in the literature review. Biogas production process can use livestock waste and vegetable or fruit waste which is included in organic waste. The effectiveness of its use is used by combining both livestock waste materials and vegetable or fruit waste with a ratio according to the amount of composition that has been determined in experimental tests in several related studies. Some studies emphasize the optimal biogas production results where the mixture of livestock waste material composition is more than vegetable and fruit waste.